Measurement and modelling of haptic textures - Guruswamy, Vijaya Lakshmi (University of Ottawa (Canada), 2009)
Haptic texture allows the user to feel the fine surface details of an object. In the absence of haptic texture, irrespective of the appearance of a virtual object, the object feels smooth. Haptic texture conveys these surface details of an object in terms of material variables - roughness and compliance. Roughness can be inferred from irregularities in the surface structure, whereas compliance can be determined from the deformation of the object when a force is applied. To model realistic haptic textures, one needs to incorporate these material variables from real world samples. Haptic texture modelling, which accurately represents the material variables from real world samples, can be a challenging task. We introduce a vibrotactile model to represent haptic textures and a statistical approach to estimate compliance from real world measurements. We measure the material variables from real life objects by simply stroking the surface with a hand-held probe. We claim that our vibrotactile model is simple and can represent both surfaces with identifiable features and stochastic nature. Our compliance estimation is carried out by analyzing the linear relationship between force and acceleration. The estimated compliance coefficients serve as a good heuristic model to render the stiffness of textures.
Keywords: Computer Science.